Association of sodium-glucose cotransporter 2 inhibitors with cardiovascular outcome and safety events: A meta-analysis of randomized controlled clinical trials - Gong, Chen; Shen, Shi-Chun; Zhang, Ke; Zhou, Lei; Shen, Jun-Jie; Zhao, Jia-Ying; Ding, Sheng-Gang; Ma, Li-kun; Gao, Hui (Frontiers in Cardiovascular Medicine, 2022)
Background The clinical benefit of sodium-glucose cotransporter 2 (SGLT2) inhibitors for preventing and treating cardiovascular events is still controversial. We aimed to study the effect of SGLT2 inhibitors on cardiovascular outcomes and safety events, with particular attention to the benefits in subgroups of patients with different diseases. Method Randomized controlled trials (RCTs) reported cardiovascular outcomes following SGLT2 inhibitors and placebo was included in this study. cardiovascular outcomes included all-cause death, major adverse cardiovascular events (MACEs), cardiovascular death (CV death), myocardial infarction (MI), stroke, hospitalization for heart failure (HHF). We also focused on the cardiovascular benefits of SGLT2 inhibitor application in subgroups of patients with different diseases, including type 2 diabetes (T2D), HF, high risk of atherosclerotic cardiovascular disease (ACD), diagnosed ACD, and chronic kidney disease (CKD). Safety events of SGLT2 inhibitors, including acute kidney injury (AKI), diabetic ketoacidosis (DKA), hypoglycemia, urinary tract infection, thromboembolic event, bone fracture, volume depletion, and amputation were reported as well. Results This meta-analysis included 15 RCTs involving 78,212 participants. SGLT2 inhibitors reduced the risk of all-cause death (RR 0.89; 95% CI: 0.85-0.94; I2=32%; p<0.01), CV death (RR 0.87; 95% CI: 0.82- 0.93; I2=11%; p<0.01), MACE (RR 0.89; 95% CI: 0.84-0.94; I2=46%; p< 0.01), HHF (RR 0.70; 95% CI: 0.66-0.74; I2=0%; p<0.01), AKI (RR 0.81; 95% CI: 0.73-0.90; I2=0%; p<0.01), increased the risk of DKA (RR 2.56; 95% CI: 1.72-3.80; I2=0%; p<0.01). However, no apparent benefit in MI and stroke was observed between the SGLT2 inhibitor and control groups. SGLT2 inhibitors reduced the risk of all-cause death, MACE, CV death, and HHF in diabetic patients; reduced the risk of all-cause death, MACE, CV death, MI, and HHF in primary prevention; reduced the risk of all-cause death, CV death, and HHF in patients with ACD and HF; and reduced the risk of MACE, CV death, and HHF in patients with CKD. Conclusion SGLT2 inhibitors have a positive effect in reducing the risk of all-cause death, CV death, MACE, HHF, AKI, and increasing the risk of DKA. The application of SGLT2 inhibitors in the primary prevention of ACD also has certain clinical benefits in reducing MI.